Effectivity Biopsychosocial intervention with Cognitive Behavioral Therapy and Exercise Therapy Program in Chronic Low Back Pain: Meta-analysis - Fadli, Arif; Prasetya, Hanung; Kristyanto, Agus (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Pain is a common complaint that causes decreased work productivity and a cause of disability. Biomedical interventions failed to inhibit the increase in chronic low back pain (CLBP) treatment costs. The pain perception of CLBP patients is influenced by emotional psychological and cognitive factors that require biopsychosocial intervention. This study aimed to summarize the existing literature data regarding the effectiveness of biopsychosocial interventions with Cognitive Behavioral Therapy (CBT) and Exercise Therapy Program (ETP) in CLBP.Subjects and Method: This research was systematic review and meta-analysis of the Randomized Control Trial study on the electronic database Pubmed, Google scholar, Willey Online Library, Research Gate, Science Direct. Data analysis was performed using the Revman 5.3 program with Cohen's effect size d.Results: There are 7 articles included in this research. The results of the analysis of studies on the effectiveness of biopsychosocial interventions for CBT and ETP in reducing the intensity of CLBP pain were very large with the effect size (d= -1.31; 95% CI= -2.39 to -0.23; p <0.001), while the effect size of the disability index was very large (d= -1.62; 95% CI= -2.70 to -0.54; p<0.001).Conclusion: Biopsychosocial interventions for CBT and ETP are effective in reducing the pain and disability index of CLBP. The effectiveness of biopsychosocial interventions with CBT and ETP methods is due to the patient's efficacy in completing the rehabilitation program.Keywords: biopysichosocial, CBT, ETP, CLBPCorrespondence: Arif Fadli. Masters Program in Public Health Sciences, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: Ariffadli950@gmail.com. Mobile: +6281355377050.Indonesian Journal of Medicine (2021), 06(02): 177-193https://doi.org/10.26911/theijmed.2021.06.02.07